ULASAN Kajian Filogenetika Molekuler dan Peranannya dalam Menyediakan Informasi Dasar untuk Meningkatkan Kualitas Sumber Genetik Anggrek - Topik Hidayat; Adi Pancoro (Jurnal AgroBiogen, 2008)
Early informationresulted from molecular phylogenetic studies of many importantornamental crops is often less attention to manygrowers and farmers. Phylogenetics is one of the most preferablemethod in systematics to reconstruct evolutionaryrelationships of groups of biological organisms in order tounderstand their biodiversities. This has been revolutionizedby DNA sequences data. In this method, a group of organismsthat shares many identical characteristics are consideredto be closely related; deriving from a commonancestor and is assumed to have similar genetic patternsand biochemical properties. By these basic principles,molecular phylogenetics plays important roles in revealing abasic knowledge on pattern of relationships to whichgenetic resources can be improved. Over the past decade,botanists have done several thousand phylogenetic analysesbased on molecular data of economically and horticulturallyimportant crops. Orchids are the best example for this.There is no doubt that most orchid plants had played roles inhorticulture and hybridization. At present, many infragenericand intergeneric hybrids are available commercially. Successfulhybridization can be achieved if two or more individualplants understudy are closely related in respect to theirgenetics and evolution.